On the relevance of the mathematics curriculum to young people - Sealey, Paula; Noyes, Andrew (Taylor and Francis Group, 2010)
In this paper we draw upon focus group data from a large study of learner trajectories through 14-19 mathematics education to think about the notion of relevance in the mathematics curriculum. Drawing on data from three socially distanced sites we explore how different emphases on what might be termed practical, process and/or professional forms of relevance affect the experiences and aspirations of learners of mathematics. We consider whether an emphasis on practical relevance in schools serving relatively disadvantaged communities might aid the reproduction of students’ social position. This leads us to suggest that a fourth category of curriculum relevance – political relevance – is largely missing from classrooms.